The impact of home medication review in patients with type 2 diabetes mellitus living in rural areas of Kuantan - Nor Elina binti Alias (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2015)
Approximately 1-in-5 Malaysians over the age of 30 have Type 2 Diabetes Mellitus (T2DM). Anti-diabetics are the most utilized prescription drugs and its expenditure is the second highest in Malaysia. Therefore it is vital to have a health program such as home medication review (HMR) to ensure the safe and quality use of medicines amongst diabetics. In Malaysia, HMR is part of the Medication Therapy Management (MTM) program, aimed at addressing appropriate medication use by extending pharmaceutical care services to eligible patients at home. This study investigated whether HMR could improve the clinical indices, quality of life and medication adherence in patients with T2DM. This was a six month prospective-randomized- controlled study. Adult patients taking medications for diabetes for at least two years, with HbA1c>8%, were recruited and randomized into intervention or control groups. The intervention group received three home visits by a pharmacist (at baseline, 3 months and during the 5th month), and one group counselling session with a dietician in addition to the standard medical care. Control group patients only received standard medical care. Primary outcome measures were HbA1c, fasting blood sugar (FBS) and blood pressure (BP). Secondary outcome measures included lipid profile (triglycerides, LDL- and HDL-cholesterol); medication adherence (assessed using Modified Morisky Adherence Scale (MMAS)); and quality of life (QoL) assessed using the Short form health survey (SF-36v2). Outcome measures were evaluated at baseline, 3 months and at 6 months.73 patients were recruited and randomized into the intervention group (38) or the control group (35), with no significant difference identified in baseline parameters. Data were analysed in SPSSv19 (IBM) using ANOVA and paired t-test. There were significant improvements from baseline to 6 months in the intervention group in HbA1c, FBS, systolic BP, diastolic BP, triglycerides and medication adherence. The control group showed no significant changes in outcome measures. QoL improved in the intervention group but declined in the control group. In conclusion, HMR conducted by a pharmacist provided significant improvement in health and QoL of patients with Type 2 Diabetes Mellitus. HMR may also be beneficial for patients with other chronic diseases and for improved healthcare system.